Expression of CD44, PCNA and E-cadherin in pterygium tissues - Humeyra Yıldırım; Gulay Turan; Meydan Turan (Indian Journal of Ophthalmology, 2024)
Purpose: Pterygium is a common ocular surface disease defined by fibrovascular conjunctival growth extending onto the cornea. However, its pathogenesis remains unclear. This study aimed to determine the role of CD44, proliferating cell nuclear antigen (PCNA), and E-cadherin in pterygium formation and recurrence. Methods: Sixty patients with pterygium participated in the study, and we collected conjunctival samples from 30 patients to form a control group. CD44, PCNA, and E-cadherin expressions in surgically excised pterygium were compared with tissue samples from the control group. Results: We observed that the percentages of CD44 and PCNA were statistically higher in the primary pterygium group and recurrent pterygium group than in the control group (P < 0.001 and P < 0.001, respectively). Conversely, E-cadherin values were statistically higher in the control group than in the primary and recurrent pterygium groups (P = 0.013 and P < 0.001, respectively). Conclusion: Cell proliferation and cell adhesion factors may play important roles in the pathogenesis of pterygium.